Perancangan E-Commerce Produk Makanan dan Kerajinan untuk Meningkatkan Penjualan UMKM di Padang Pariaman - Fahira Risna, Rahma; Annas, Firdaus; Nesa Yolanda, Dinda; Wandira, Raju; Alwi, Muhammad (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The purpose of this article is to design an appropriate e-commerce platform to promote food and craft products from MSMEs in Padang Pariaman, with the hope of increasing sales and product competitiveness. Currently, the majority of sales of food products are still done traditionally or manually, although some food products have started to use social media as a promotional medium. Meanwhile, sales of handicraft products are generally still carried out traditionally and are not yet widely known. In fact, the rapid advances in information and communication technology currently provide great opportunities for the spread of food and craft products to be known globally. This research uses the Research and Development (RnD) method with the Define, Design, Develop, and Decemination development model, which aims to produce effective and efficient solutions. The research results show that the use of the OpenCart application as a web-based promotional media is proven to be valid, practical, effective and efficient, and is able to have a positive impact on increasing product visibility and competitiveness. The results of this research show that OpenCart can be used as a strategic platform to promote MSME food and craft products, with the aim of increasing competitiveness and wider market access for local products in Padang Pariaman. Thus, it is hoped that e-commerce can support the development of MSMEs and improve the regional economy.